Data collection and analysis for the development of environmental resilience index in Selangor / Sharifah Husna Syed Zainal Yussof ... [et al.] - Syed Zainal Yussof, Sharifah Husna; Asmawi, M. Zainora; Ibrahim, Illyani; Wan Mohd Rani, Wan Nurul Mardhiah (UiTM Press, 2021)
Over the years, population surges resulted in urban sprawl in meeting the needs and demands of the future generation. However, excessive human activities in the environment cause environmental degradation, which affects cities resilience. In addition, the impact of global climate change has significantly affected the local environmental context in many towns. As a result, we experience constant incidences of natural disasters, such as monsoon floods, flash floods and landslides. The absence of a framework to address the resilience level in Selangor may lead to a problematic situation in planning and managing the development concerning the physical contexts, for instance, the location and topographic aspects. Therefore, this paper introduces the research to develop an Environmental Resilience Index (ERI) to measure Malaysia's level of environmental resilience by selecting Selangor as a case study because of the difference in economic activities that could result in different levels of environmental resilience. This paper also explains the general framework and indicator selected for this study by reviewing environmental systems and reviews of past research and established indicators. Though this study uses secondary data as the basis of data collection, data from authorised departments and agencies are gathered to verify the reliability and validity of data essential in the analysis stage. Lastly, this paper elaborates on the methodology of data collection and data analysis with an example by measuring the ERI level for the component of environmental resources for the district of Kuala Selangor. Considering the latest secondary data, the results demonstrate that Selangor has an ERI of moderate level for the component of environmental resources.